Delayed Absorption of Subretinal Fluid after Retinal Reattachment Surgery and Associated Choroidal Features - Kim, Jong Min (Korean J Ophthalmol, 2017)
PURPOSE: The aim of this study was to investigate the incidence and associated clinical factors of delayed absorption of subretinal fluid (SRF) after surgery for rhegmatogenous retinal detachment. METHODS: This study involved 36 eyes of 36 consecutive patients who underwent successful surgery for rhegmatogenous retinal detachment. A complete ophthalmologic evaluation, including clinical fundus examination, optical coherence tomography, and indocyanine green angiography, was conducted before and after surgery. Delayed absorption was defined as the presence of residual concave SRF or an SRF bleb at 6 months after surgery. Clinical factors and choroidal features on indocyanine green angiography were compared according to the presence and absence of delayed absorption. RESULTS: Eighteen of 36 eyes (50%) showed delayed absorption. Macular involvement and worse preoperative visual acuity were significantly related to the presence of delayed absorption (p = 0.001 and p = 0.034, respectively). On indocyanine green angiography, preoperative choroidal vascular hyperpermeability was noted in 70% of eyes with delayed absorption and in 14% of eyes without it (p = 0.010). CONCLUSIONS: Delayed absorption of SRF after retinal reattachment surgery was not rare, with a 50% of incidence in this study. Macula-off status was significantly related to the incidence of delayed SRF absorption, and choroidal features such as choroidal vascular hyperpermeability might be responsible in part, possibly through the resultant exudative property of choroid.